SPATIAL AND TEMPORAL DISTRIBUTION OF RAINFALL EROSIVITY IN BRAZILIAN AMAZONIA: A HYDROLOGICAL PERSPECTIVE BASED ON CMORPH TECHNIQUE - Souto, Jefferson Inayan de Oliveira; Lobato, Richard Reno da Costa; Lima, Ilale Ferreira; Pfeiff, Greicy Kelly; Brenda Caroline Sampaio da Silva (Caminhos de Geografia, 2022)
Rainfall erosivity is one crucial factor that controls soil erosion. The interannual variability of rainfall erosivity in Brazilian Amazonia connected to the El Niño-Southern Oscillation. This paper presents a study of the effects of Sea Surface Temperatures anomalies for El Niño region on rainfall erosivity in the Brazilian Amazonia. Rainfall erosivity across was assessed using 30 minutes rainfall data from Climate Prediction Center MORPHing technique during the period from 1998 to 2019. Results indicated that average rainfall erosivity is stronger during La Niña events and weaker during El Niño events. The annual value of rainfall erosivity ranged from 8241 to 24310 (Mj mm ha−1 h−1 year−1). Results also indicated that the effects of extending northward over Brazilian Amazonia showed a significant correlation (P <0.05) between annual rainfall erosivity and annual precipitation. The El Niño-Southern Oscillation conditions was determined to exert the most substantial influence on rainfall erosivity. This information would be useful in the implementation of new soil conservation strategies.